Biosynthesis and Optimization of PolyHydroxyalkanoate (PHA) Production by Acinetobacter lwoffii Isolate - Karrar Hameed; Iman Gatea; Amal Hussein (Journal of Applied Sciences and Nanotechnology, 2023)
Polyhydroxyalkanoate (PHA) is an eco-friendly polymer that has various important biomedical uses, as well as biodegradability, drug delivery, and medical implants. It is a kind of polyester synthesized by various microorganisms as energy reserve material under inappropriate conditions. This study focused on testing wastecooking oilas the source of carbon to optimize PHA production. The tests included the most important environmental components within the culture medium affecting the growth of the bacterial isolate under the experiment and its ability to produce a polymer. Results revealed that the cultivation of Acinetobacter lwoffii, pre-isolated from hydrocarbon contaminated soil, under optimum conditions showed the highest productivity after 72 hours. Corn oil waste as the carbon and urea as the source of nitrogen were discovered to be the best nutritive sources for concentrated PHA production, with, 2% and 0.5 g/L as the best carbon and nitrogen sources concentrations, respectively. Through the results, it was found that there is an important role for the change, both qualitatively and quantitatively, in the components of the nutrient medium and the surrounding condition in increasing the efficiency of isolation, as it had a significant role in increasing the efficiency of the isolate. There was a significant increase in the PHA content ranging from 10 to 75% and the production of biomass to 3.6 g/L. respectively. Finally, this study concluded that the use of bacterial isolate in the production of PHA can contribute to solving the critical problem of environmental pollution caused by the use of industrial plastic and replacing it with environmentally friendly and low-cost materials.